Interaksi sel-sel imunokompeten pada asma bronkiale - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Key words: bronchial asthma - immunocompetent cell interactions - T-cell subpopulations - T-cell cytokiness - mucosal IgA response